Spatial Dynamics of Natural Regeneration in Two Differently Managed Pinus sylvestris Stands before and after Silvicultural Intervention Using Replicated Spatial Point Patterns - Pardos, Marta; Montes, Fernando; Canellas, Isabel (Forest science, 2008)
Individual seedlings were mapped on eight 5 m × 5 m plots between 2003 and 2006, in two differently managed Pinus sylvestris forests in Spain (group shelterwood system in Valsaín forest versus uniform system followed by soil preparation in Navafría forest). The spatial pattern of the seedlings was analyzed through the L(d) function. The spatial relationship between seedlings before and after the regeneration felling was analyzed using the intertype L(rs) (d) function. To study the spatial relationship between seedling distribution and either light availability or organic matter depth, the K(rx) (d) function was used. A practical method is proposed for obtaining the group-specific mean for several replicates: L(std)(d), based on the standardization of the L(d) function by the quantile bounds of the null model, which, once attained, is compared with the sum, weighted by the number of points in each replicate. Both the L(std)(d) group means and the point number weighted mean showed a cluster pattern for seedlings from germination to 6 years old, peaking at short scales (15-100 cm), before and after the cutting. After the cutting, the co-occurrence between germinants and older seedlings was not significant, although the L(rs) (d) function was positive and presented a peak (50-100 cm). Seedling emergence was positively associated with organic matter depth after the cutting. The association between seedling distribution and light was modified when the cutting was severe (>60% of tree basal area).